Riflessioni con Vincenzo Cabianca sulle Isole Eolie - Costa, Giorgio (Ri-Vista. Research for landscape architecture, 2015)
With Vincenzo Cabianca, planner of Aeolian Islands landscape, we talk about scientific knowledge and landscape planning in small islands. In particular, when natural system is so strongly giving shape from the viewpoint of geophysics and vulcanology. During the discussion we carry out deep reflections upon significant of cultural heritage and insularity in this geographical contest, so unique like an insular Vulcan arc can be. Before partially lived in, then place of permanent and productive life, today archipelago’s landscape plan challenges the strong tourist pressure and business to protect his cultural scientific heritage, subject of specific international research.